Oligomerization Profile of Human Transthyretin Variants with Distinct Amyloidogenicity - Frangolho, Ana (2020)
One of the molecular hallmarks of amyloidoses is ordered protein aggregation involving the initial formation of soluble protein oligomers that eventually grow into insoluble fibrils. The identification and characterization of molecular species critical for amyloid fibril formation and disease development have been the focus of intense analysis in the literature. Here, using photo-induced cross-linking of unmodified proteins (PICUP), we studied the early stages of oligomerization of human transthyretin (TTR), a plasma protein involved in amyloid diseases (ATTR amyloidosis) with multiple clinical manifestations. Upon comparison, the oligomerization processes of wild-type TTR (TTRwt) and several TTR variants (TTRV30M, TTRL55P, and TTRT119M) clearly show distinct oligomerization kinetics for the amyloidogenic variants but a similar oligomerization mechanism. The oligomerization kinetics of the TTR amyloidogenic variants under analysis showed a good correlation with their amyloidogenic potential, with the most amyloidogenic variants aggregating faster (TTRL55P > TTRV30M > TTRwt). Moreover, the early stage oligomerization mechanism for these variants involves stepwise addition of monomeric units to the growing oligomer. A completely different behavior was observed for the nonamyloidogenic TTRT119M variant, which does not form oligomers in the same acidic conditions and even for longer incubation times. Thorough characterization of the initial steps of TTR oligomerization is critical for better understanding the origin of ATTR cytotoxicity and developing novel therapeutic strategies for the treatment of ATTR amyloidosis.